Navigating Risk and Profit in Sharia Investment: Its Impact on MSME Sustainability in Central Java with a Focus on Social Investment - Andiani, Paramita; Hendratri, Bhaswarendra Guntur; Novitasari, Salwa Aulia (West Science Social and Humanities Studies, 2025)
This study examines the impact of risk and profit on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Central Java, focusing on the mediating role of social investment within Sharia-compliant financial practices. Employing a quantitative approach, data were collected from 85 MSMEs through structured questionnaires and analyzed using SPSS version 25. The findings reveal that financial risk negatively affects MSME sustainability, while profitability positively influences it. Social investment practices, such as zakat and waqf, play a significant mediating role, reducing the negative impact of risk and enhancing the positive influence of profitability on sustainability. These results highlight the importance of integrating ethical and socially responsible financial practices in fostering resilience and growth among MSMEs. The study underscores the potential of Sharia investment principles in addressing the unique challenges faced by MSMEs, offering practical insights for policymakers and business stakeholders.